2011
DOI: 10.1097/ta.0b013e31820e7ca1
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Arterial Embolization in the Management of Blunt Hepatic Trauma: Indications and Complications

Abstract: AE is a key element in modern management of high-grade liver injuries. Two principal indications exist in the acute postinjury phase: primary hemostatic control in hemodynamically stable or stabilized patients with radiologic computed tomography evidence of active arterial bleeding and adjunctive hemostatic control in patients with uncontrolled suspected arterial bleeding despite emergency laparotomy. Successful management of injuries of grade III upward often entails a combined angiographic and surgical appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 23 publications
0
67
0
6
Order By: Relevance
“…In the report with the largest number of the cases [5], 30 of 71 (42.3%) patients who had a high-grade liver injury developed hepatic infarction after TAE; 2 of those 30 died of hepatic infarction. In other reports, 1 of 14 (7.1%) patients [4], 3 of 23 (13.0%) patients [7], 3 of 23 (13.0%) patients [8], and 7 of 31 (22.6%) patients [9] developed hepatic infarction. There was one fatality in each of these reports.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…In the report with the largest number of the cases [5], 30 of 71 (42.3%) patients who had a high-grade liver injury developed hepatic infarction after TAE; 2 of those 30 died of hepatic infarction. In other reports, 1 of 14 (7.1%) patients [4], 3 of 23 (13.0%) patients [7], 3 of 23 (13.0%) patients [8], and 7 of 31 (22.6%) patients [9] developed hepatic infarction. There was one fatality in each of these reports.…”
Section: Discussionmentioning
confidence: 69%
“…after TAE for trauma [4,5,[7][8][9]. In the report with the largest number of the cases [5], 30 of 71 (42.3%) patients who had a high-grade liver injury developed hepatic infarction after TAE; 2 of those 30 died of hepatic infarction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Letoublon et al described a 70% morbidity rate in 23 patients treated with TAE [25]. According to the author, however, complications are not exclusively caused by the procedure itself, but also a consequence of complexity of liver trauma.…”
Section: Transarterial Angiographic Embolization (Tae)mentioning
confidence: 99%
“…67 HAE is also used in selective embolisation of deep hepatic parenchymal bleeding in haemodynamically unstable patients with a grade 3 and above liver injury after a damage control laparotomy. 68,69 Liver-related complications of HAE (bile leaks, abscesses, and liver and gallbladder necrosis) run high (50-70%) 67,69 but selective HAE may reduce the latter. 70 HAE use has increased in trauma and it has been suggested that surgery may become an adjunct to HAE in level 1 trauma centres in those patients with borderline haemodynamic instability.…”
Section: Hepatic Injuriesmentioning
confidence: 99%